CREDIT CARD - A WAY TO GENERATE LEGITIMATEMONEY FOR PAYMENTS - Regi., S.Bulomine (International Journal of Research -GRANTHAALAYAH, 2016)
This paper discusses on credit card features, advantages and disadvantages. It helps the reader to enrich themselves in knowing about credit card in detail. Credit cards enable an individual to purchase products or services without paying immediately. The buyer only needs to present the credit cards at the cash counter and sign the bill. Credit card can, therefore, be considered as a good substitute for cash or cheques. A Credit card is a card or mechanism which enables cardholders to purchase goods, travel and dine in a hotel without making immediate payments. The main objective of this paper is to identify and study the advantages and disadvantages of using credit card. From this paper, it is observed that credit card is boon if the credit cardholder used with special care, otherwise the cardholder has to face deficit in their course of time.